High-purity silicon carbide ceramic material and preparation method thereof

By using polycrystalline silicon powder and high-purity carbon powder in silicon carbide materials, and adding additives such as polycarbosilane for sintering preparation, the problem of high impurity content in traditional silicon carbide materials is solved, and the purity and performance of the material are improved.

CN119330718APending Publication Date: 2025-01-21NANTONG SANZER PRECISION CERAMICS CO LTD +1

Patent Information

Application Number
CN202411413376.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Due to the high impurity content of traditional sintered silicon carbide materials, they are prone to volatile contamination due to impurities during use, affecting the chip quality.

Method used

By designing the silicon carbide material composition and preparation method, polycrystalline silicon powder and high-purity carbon powder are used to synthesize silicon carbide powder, and additives such as polycarbosilane are added for sintering preparation to improve the purity and density of the material.

Benefits of technology

It improves the purity and density of sintered silicon carbide ceramic materials, reduces impurity volatilization pollution, and improves the material's bending strength, thermal conductivity and fracture toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078644250000051
    Figure BDA0005078644250000051
  • Figure BDA0005078644250000061
    Figure BDA0005078644250000061
  • Figure BDA0005078644250000171
    Figure BDA0005078644250000171
Patent Text Reader

Abstract

The invention provides a high-purity silicon carbide ceramic material which is of a structure prepared by adding an additive into silicon carbide powder prepared from polycrystalline silicon powder and high-purity carbon powder and sintering, the silicon carbide powder comprises one or more of a 4H crystal form, a beta crystal form and an alpha crystal form, and the additive is polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nanowhiskers; wherein the molar ratio of the silicon powder to the carbon powder is 1: (1-1.1); and the additive accounts for 0-1% of the total mass of the silicon carbide powder and the additive powder. Meanwhile, the invention further provides a preparation method of the material, impurities in the raw materials are effectively removed through a liquid phase reaction, the purity of the raw material powder is improved from the source, and the problem that the impurities of the silicon carbide powder are difficult to remove is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon carbide ceramics and preparation processes, and in particular relates to a high-purity silicon carbide ceramic material and a preparation method. Background Art

[0002] Silicon carbide ceramics have excellent properties, such as high hardness, high strength and high thermal conductivity, and can be applied to various bearing components with high mechanical strength requirements. In addition, silicon carbide also has excellent oxidation resistance, creep resistance and other characteristics, and can be applied to high temperature resistant bearing components. With the development of my country's semiconductor industry, the demand for manufacturing equipment in the semiconductor industry has increased dramatically. Silicon carbide crystal boats, silicon carbide suction cups and silicon carbide carriers are important tools in the chip production process, and their quality directly affects the quality of the chip. Due to the high impurity content, traditional sintered silicon carbide materials are easily contaminated by volatile impurities during use, affecting the quality of the chip and further affecting chip production. Therefore, traditional silicon carbide tools must prepare high-purity silicon carbide coatings on their surfaces to close their surface pores and inhibit the influence of their high-temperature volatile impurities on the chip. In the present invention, by designing the composition and preparation method of silicon carbide materials, the problem of high impurity content of traditional sintered silicon carbide materials is solved, the purity of sintered silicon carbide ceramic materials is improved, and the problem of sintered silicon carbide ceramics needing to be prepared by coating to close impurity volatile pollution is avoided. Summary of the invention

[0003] Technical solution: In order to solve the above technical problems, the present invention provides a high-purity silicon carbide ceramic material. The ceramic material is a structure prepared by sintering silicon carbide powder prepared from polycrystalline silicon powder and high-purity carbon powder, and adding additives; the silicon carbide powder includes one or more of 4H crystal type, β crystal type, and α crystal type, and the additive is polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nano whiskers; the molar ratio of silicon powder to carbon powder is silicon powder: high-purity carbon powder = 1:1-1.1; the additive accounts for 0-1% of the total mass of silicon carbide powder and additive powder, and the impurity content in the high-purity carbon powder is <400ppm.

[0004] As an improvement, the density of the high-purity silicon carbide ceramic material is 2.8-3.1 g / cm 3 , porosity is 0-0.5%, impurity content is <500ppm, bending strength is 130-250MPa, thermal conductivity is 110-140W / (m·K), thermal expansion coefficient is 3-8K -1 ×10 -6 , fracture toughness 3~7MPa·m 1 / 2 .

[0005] At the same time, the present invention also provides a method for preparing the above-mentioned high-purity silicon carbide ceramic material, and the specific steps of the method include:

[0006] (1) Preparation and purification of silicon carbide powder

[0007] (1.1) Weigh a certain mass ratio of polycrystalline silicon blocks and silicon carbide balls, place the polycrystalline silicon blocks in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder;

[0008] (1.2) sieving and classifying the silicon powder obtained in step (1.1) to obtain classified silicon powder;

[0009] (1.3) adding the classified silicon powder and high-purity carbon powder into a phenolic resin ball mill, using deionized water as the grinding medium and phenolic resin balls for wet ball milling; wherein the impurity content in the high-purity carbon powder is less than 400ppm;

[0010] (1.4) After the grinding in step (1.3) is completed, sulfuric acid is added to the ground slurry and the grinding is continued;

[0011] (1.5) After the grinding in step (1.4) is completed, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is >4;

[0012] (1.6) taking out the filter cake from step (1.5) and drying it at 80-200° C. for 0.5-5 h;

[0013] (1.7) The dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree below 1.5 MPa;

[0014] (1.8) Sintering and heat preservation are performed in a vacuum sintering furnace under a temperature rising program, and high-purity silicon carbide powders of different crystal forms are obtained after cooling in the furnace, and high-purity silicon carbide powders are obtained after crushing and grinding, sieving, and grading;

[0015] (2) Preparation of silicon carbide ceramic materials

[0016] (2.1) adding a high-purity additive to the obtained high-purity silicon carbide powder, and stirring the mixture to obtain a mixed powder;

[0017] (2.2) pouring the mixed powder in step (2.1) into a mold, and preparing a green blank by dry pressing, the dry pressing pressure being 5 to 20 MPa;

[0018] (2.3) placing the green blank in step (2.2) into a vacuum sintering furnace and evacuating the vacuum to 0.5-1.5 MPa, maintaining the vacuum, and heating the temperature to 1600-1800° C. at a heating rate of 3-8° C. / min, and then introducing argon gas into the vacuum sintering furnace;

[0019] (2.4) Continue to heat the vacuum sintering furnace in step (2.3) to 1900° C. to 2200° C., keep the temperature for 1 to 4 hours, and then cool the furnace to obtain a high-purity silicon carbide ceramic material.

[0020] As an improvement, in step (1), the mass ratio of polycrystalline silicon blocks to silicon carbide balls is polycrystalline silicon: silicon carbide balls = 1:0.4-0.8; the spherical ink time is 1-48 hours; and the size of the silicon powder after classification is 80-400 μm.

[0021] As an improvement, in step (1.3), the molar ratio of silicon powder to carbon powder is silicon powder: high-purity carbon powder = 1:1 to 1.1.

[0022] As an improvement, in step (1.3), the mass ratio of deionized water to powder is deionized water: powder = 0.6-0.9:1.

[0023] As an improvement, in step (1.4), the ball milling time is 1 to 20 hours.

[0024] As an improvement, the heating program includes one or more of the following:

[0025] (1.8.1) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min and kept at this temperature for 2-8 hours. After cooling in the furnace, high-purity silicon carbide of β-crystal form is obtained;

[0026] (1.8.2) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min, and kept at this temperature for 2-8 hours, and then the temperature is further increased to 1400-1600°C at a heating rate of 2-5°C / min, and kept at this temperature for 1-4 hours, and then cooled in the furnace to obtain high-purity silicon carbide of 4H crystal form;

[0027] (1.8.3) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min and kept at this temperature for 2-8 hours. The temperature is then raised to 1400-1600°C at a heating rate of 2-5°C / min and kept at this temperature for 1-4 hours. The temperature is then raised to 2000-2300°C at a heating rate of 2-5°C / min and kept at this temperature for 1-4 hours. The furnace is then cooled to obtain high-purity silicon carbide in the α-crystalline form.

[0028] As an improvement, in step (1.8), the size of the high-purity silicon carbide powder obtained after classification is 80 to 500 μm.

[0029] As an improvement, in step (2.1), the additive is one or more of polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nanowhiskers; the impurity content thereof is less than 400 ppm, and the amount of the additive added is 0 to 1% of the total mass of the powder.

[0030] Beneficial effects: Compared with conventional materials, the materials and preparation methods proposed in the present invention have the following advantages:

[0031] (1) In the present invention, silicon powder and high-purity carbon powder are directly ground and reacted with acid, and impurities in the raw materials are effectively removed by liquid phase reaction, thereby improving the purity of the raw material powder from the source and avoiding the problem of difficulty in removing impurities from silicon carbide powder;

[0032] (2) In the present invention, liquid silicon carbide is produced at low temperature by using additives, and liquid silicon carbide is used as a reaction initiator, thereby solving the problem of high reaction initiation temperature and difficult reaction in the process of directly reacting silicon powder and carbon powder to generate silicon carbide.

[0033] (3) In the present invention, by using additives, a silicon carbide liquid phase is generated at a low temperature, and the liquid phase silicon carbide is used as a binder to fully fill the gaps between silicon carbide particles, thereby improving the densification degree of the silicon carbide material. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0035] In the present invention, high-purity silicon carbide ceramic material is prepared by first removing impurities from silicon powder, purifying it, and then reacting it with high-purity carbon powder to prepare high-purity silicon carbide powder. This is different from the traditional process of first preparing silicon carbide powder and then removing impurities. It avoids the problem of difficulty in removing coated metal impurities due to the coating effect of silicon carbide in the traditional process.

[0036] Furthermore, the present invention provides a method for preparing a high-purity silicon carbide ceramic material, the specific steps of which include:

[0037] Weigh polycrystalline silicon blocks and silicon carbide balls in a certain mass ratio, first place the polycrystalline silicon blocks in a silicon carbide ball-inking tank, and add silicon carbide balls for spheroidal inking to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain classified silicon powder; wherein the mass ratio of the polycrystalline silicon blocks to the silicon carbide balls is 0.4-0.8; the spheroidal inking time is 1-48h; the size of the silicon powder after classification is 80-400μm.

[0038] The classified silicon powder and high-purity carbon powder are added into a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 1 to 20 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1 to 1.1, and the mass ratio of deionized water to powder is 0.6 to 0.9:1.

[0039] When the grinding is completed, sulfuric acid is added to the ground slurry and the grinding is continued; after the grinding is completed, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 80-200°C for 0.5-5h; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and the vacuum is evacuated to a vacuum degree of less than 1.5MPa; sintering and heat preservation are carried out in the vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 80-500μm.

[0040] The heating program includes one or more of the following, specifically:

[0041] (1) heating the vacuum sintering furnace to 1000-1300° C. at a heating rate of 2-10° C. / min, and keeping the temperature for 2-8 hours, and cooling the furnace to obtain high-purity silicon carbide of β-crystal form;

[0042] (2) heating the vacuum sintering furnace to 1000-1300° C. at a heating rate of 2-10° C. / min, and keeping the temperature for 2-8 hours, then heating the vacuum sintering furnace to 1400-1600° C. at a heating rate of 2-5° C. / min, and keeping the temperature for 1-4 hours, and then cooling the furnace to obtain high-purity silicon carbide of 4H crystal form;

[0043] (3) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min, and kept at this temperature for 2-8 hours. The temperature is then continuously heated to 1400-1600°C at a heating rate of 2-5°C / min, and kept at this temperature for 1-4 hours. The temperature is then continuously heated to 2000-2300°C at a heating rate of 2-5°C / min, and kept at this temperature for 1-4 hours. The furnace is then cooled to obtain high-purity silicon carbide of α-crystal form.

[0044] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is one or more of polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nano whisker; and the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 5 to 20 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to a vacuum of 0.5 to 1.5 MPa, and the vacuum is maintained, and the temperature is increased to 1600 to 1800° C. at a heating rate of 3 to 8° C. / min, and argon gas is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 1900 to 2200° C., and the temperature is kept for 1 to 4 hours, and the mixture is cooled along with the furnace to obtain a high-purity silicon carbide ceramic material.

[0045] In order to better explain and illustrate the present invention, specific embodiments are described below.

[0046] Example 1

[0047] Ten experimental groups were selected, and different ratios of silicon powder and carbon powder and different impurity contents were set to obtain silicon carbide with different crystal forms according to the heating program. The specific parameters are shown in Table 1.

[0048] Table 1. Parameter settings during preparation in experimental groups 1-10

[0049]

[0050] According to the parameters in Table 1, other steps are the same, and the final silicon carbide ceramic material is tested for its performance, as shown in Table 2.

[0051] Table 2 Properties of silicon carbide materials obtained in experimental groups 1-10

[0052]

[0053] As shown in Table 1, it can be obtained that at different reaction ratios, the impurity content is maintained between 300 and 400 ppm. As the carbon content increases, the impurities increase slightly, mainly unreacted carbon.

[0054] As shown in Table 2, at different reaction ratios, the impurity content is maintained between 300 and 400 ppm, and the appropriate carbon-silicon ratio, the bending strength and thermal conductivity of silicon carbide ceramics are the largest, and the thermal expansion coefficient and fracture toughness are moderate.

[0055] Example 2

[0056] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.4, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 400μm; the spherical ink time is 48h;.

[0057] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 1 hour; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1, and the mass ratio of deionized water to powder is 0.9:1.

[0058] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. Deionized water is continuously added to rinse the filter cake during the suction filtration process until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 80°C for 0.5h; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5MPa; sintering and insulation are performed in a vacuum sintering furnace under a heating program, and high-purity silicon carbide powder of different crystal forms is obtained after cooling with the furnace, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 80μm.

[0059] The specific heating program is: the vacuum sintering furnace is heated to 1050°C at a heating rate of 2°C / min and kept at this temperature for 2.8 hours. After cooling in the furnace, high-purity silicon carbide of β-crystal form is obtained.

[0060] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilane and polycarbosilazane; the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 5 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.5 MPa, and the vacuum is maintained, and the temperature is increased to 1800°C at a heating rate of 3°C / min, and argon gas is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 1900°C, and after the heat preservation time is 4 hours, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0061] The obtained silicon carbide ceramic material has an impurity content of 410ppm, a bending strength of 130MPa, a thermal conductivity of 120W / (m·K), and a thermal expansion coefficient of 5K -1 ×10 -6 , fracture toughness 6MPa·m 1 / 2 .

[0062] Example 3

[0063] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.8, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 80μm; the spherical ink time is 18h.

[0064] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 12 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.1, and the mass ratio of deionized water to powder is 0.6:1.

[0065] When the grinding is completed, sulfuric acid is added to the ground slurry and the grinding is continued; after the grinding is completed, the slurry is transferred to the filtration device, and the liquid phase is removed by filtration. During the filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 200°C for 5 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and the vacuum is evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are carried out in the vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 500 μm.

[0066] The specific heating program is: the vacuum sintering furnace is heated to 1300°C at a heating rate of 10°C / min and kept at this temperature for 5 hours. After the furnace is cooled, high-purity silicon carbide of β crystal form is obtained.

[0067] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilane; the impurity content thereof is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 20MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 0.5MPa, and the vacuum is maintained, and the temperature is increased to 1600°C at a heating rate of 8°C / min, and argon gas is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2200°C, and after the heat preservation time is 1h, the mixture is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0068] The obtained silicon carbide ceramic material has an impurity content of 390ppm, a bending strength of 250MPa, a thermal conductivity of 140W / (m·K), and a thermal expansion coefficient of 3K -1 ×10 -6 , fracture toughness 4MPa·m 1 / 2 .

[0069] Example 4

[0070] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.6, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 300μm; the spherical ink time is 2h.

[0071] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 10 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.05, and the mass ratio of deionized water to powder is 0.7:1.

[0072] When the grinding is completed, sulfuric acid is added to the ground slurry and the grinding is continued; after the grinding is completed, the slurry is transferred to the suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 100°C for 1.5h; the dried filter cake is placed in a graphite mold and built into a vacuum sintering furnace, and the vacuum is evacuated to a vacuum degree of less than 1.5MPa; sintering and heat preservation are carried out in the vacuum sintering furnace under the heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder. The size of the high-purity silicon carbide powder after classification is 420μm.

[0073] The specific heating program is as follows: the vacuum sintering furnace is heated to 1000°C at a heating rate of 2°C / min, and kept warm for 6 hours, then the temperature is further heated to 1400°C at a heating rate of 5°C / min, and kept warm for 1.5 hours, and then cooled with the furnace to obtain high-purity silicon carbide with 4H crystal form.

[0074] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is silicon carbide nano whiskers; the impurity content of the mixed powder is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 15MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 5°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2000°C, and the heat preservation time is 2h, and the mixture is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0075] The obtained silicon carbide ceramic material has an impurity content of 450ppm, a bending strength of 200MPa, a thermal conductivity of 115W / (m·K), and a thermal expansion coefficient of 4.5K -1 ×10 -6 , fracture toughness 4.8MPa·m 1 / 2 .

[0076] Example 5

[0077] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.5, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 300μm; the spherical ink time is 18h.

[0078] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 1 to 20 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.01, and the mass ratio of deionized water to powder is 0.8:1.

[0079] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 120°C for 5 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are performed in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 300 μm.

[0080] The specific heating program is as follows: the vacuum sintering furnace is heated to 1300°C at a heating rate of 10°C / min, and kept warm for 6 hours, then the temperature is further heated to 1600°C at a heating rate of 3°C / min, and kept warm for 4 hours, and then cooled with the furnace to obtain high-purity silicon carbide with 4H crystal form.

[0081] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosiloxane; the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 11 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 0.75 MPa, and the vacuum is maintained, and the temperature is increased to 1650°C at a heating rate of 4.6°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 1950°C, and the heat preservation time is 2.2 hours, and the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0082] The obtained silicon carbide ceramic material has an impurity content of 415ppm, a bending strength of 165MPa, a thermal conductivity of 125W / (m·K), and a thermal expansion coefficient of 4.8K -1 ×10 -6 , fracture toughness 6.1MPa·m 1 / 2 .

[0083] Example 6

[0084] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.44, first place the polycrystalline silicon block in a silicon carbide spheroidal graphite tank, and add silicon carbide balls for spheroidal graphite to obtain silicon powder; the obtained silicon powder is sieved and graded to obtain the graded silicon powder, and the size of the graded silicon powder is 220μm; the spheroidal graphite time is 23h;.

[0085] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 12 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.04, and the mass ratio of deionized water to powder is 0.7:1.

[0086] When the grinding is completed, sulfuric acid is added to the ground slurry and the grinding is continued; after the grinding is completed, the slurry is transferred to the suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 200°C for 0.5h; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and the vacuum is evacuated to a vacuum degree of less than 1.5MPa; sintering and heat preservation are carried out in the vacuum sintering furnace under the heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 250μm.

[0087] The specific heating program is as follows: the vacuum sintering furnace is heated to 1000°C at a heating rate of 2°C / min, and kept warm for 2 hours, then the temperature is continuously increased to 1600°C at a heating rate of 5°C / min, and kept warm for 4 hours, then the temperature is continuously increased to 2000°C at a heating rate of 2°C / min, and kept warm for 2 hours, and then the furnace is cooled to obtain high-purity silicon carbide of α crystal form.

[0088] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosiloxane and silicon carbide nano whiskers; the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 11 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.1 MPa, and the vacuum is maintained, and the temperature is increased to 1680°C at a heating rate of 4.5°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2100°C, and the heat preservation time is 2.4 hours, and the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0089] The obtained silicon carbide ceramic material has an impurity content of 360ppm, a bending strength of 150MPa, a thermal conductivity of 121W / (m·K), and a thermal expansion coefficient of 6.6K -1 ×10 -6 , fracture toughness 4.5MPa·m 1 / 2 .

[0090] Example 7

[0091] Weigh polycrystalline silicon blocks and silicon carbide balls in a mass ratio of 0.5, first place the polycrystalline silicon blocks in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 80-400μm; the spherical ink time is 1-48h.

[0092] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 12 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.09, and the mass ratio of deionized water to powder is 0.78:1.

[0093] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. Deionized water is continuously added to rinse the filter cake during the suction filtration process until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 140°C for 3.5 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are performed in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 150μm.

[0094] The specific heating program is as follows: the vacuum sintering furnace is heated to 1300°C at a heating rate of 10°C / min, and kept warm for 5 hours, then the temperature is continuously increased to 1400°C at a heating rate of 3°C / min, and kept warm for 4 hours, then the temperature is continuously increased to 2300°C at a heating rate of 5°C / min, and kept warm for 2 hours, and then the furnace is cooled to obtain high-purity silicon carbide of α crystal form.

[0095] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilazane and polycarbosiloxane; the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 12 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.0 MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 4°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2100°C, and the heat preservation time is 1.5 hours, and the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0096] The obtained silicon carbide ceramic material has an impurity content of 390ppm, a bending strength of 210MPa, a thermal conductivity of 125W / (m·K), and a thermal expansion coefficient of 6.8K-1 ×10 -6 , fracture toughness 7MPa·m 1 / 2 .

[0097] Example 8

[0098] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.65, first place the polycrystalline silicon block in a silicon carbide spheroidal graphite tank, and add silicon carbide balls for spheroidal graphite to obtain silicon powder; the obtained silicon powder is sieved and graded to obtain the graded silicon powder, and the size of the graded silicon powder is 240μm; the spheroidal graphite time is 34h.

[0099] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 1 to 20 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.06, and the mass ratio of deionized water to powder is 0.7:1.

[0100] When the grinding is completed, sulfuric acid is added to the ground slurry and the grinding is continued; after the grinding is completed, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 160°C for 0.5 to 5 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and the vacuum is evacuated to a vacuum degree of less than 1.5 MPa; sintering and heat preservation are carried out in the vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 300 μm.

[0101] The heating program includes:

[0102] (1) heating the vacuum sintering furnace to 1200° C. at a heating rate of 5.5° C. / min and keeping the temperature for 4 hours, and then cooling the furnace to obtain high-purity silicon carbide of β-crystal form;

[0103] (2) The vacuum sintering furnace was heated to 1000°C at a heating rate of 7°C / min and kept at this temperature for 3.5 hours, and then the temperature was further heated to 1450°C at a heating rate of 4°C / min and kept at this temperature for 2.4 hours. After the furnace was cooled, high-purity silicon carbide of 4H crystal form was obtained.

[0104] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilazane and polycarbosiloxane; the impurity content thereof is less than 400 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 15 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 0.78 MPa, and the vacuum is maintained, and the temperature is increased to 1680°C at a heating rate of 6.8°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2000°C, and after the heat preservation time is 2 hours, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0105] The obtained silicon carbide ceramic material has an impurity content of <500ppm, a bending strength of 178MPa, a thermal conductivity of 130W / (m·K), and a thermal expansion coefficient of 5K -1 ×10 -6 , fracture toughness 6.5MPa·m 1 / 2 .

[0106] Example 9

[0107] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.48, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 180μm; the spherical ink time is 28h.

[0108] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 15 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.01, and the mass ratio of deionized water to powder is 0.9:1.

[0109] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. Deionized water is continuously added to rinse the filter cake during the filtration process until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 150°C for 3.1 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are carried out in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 350μm.

[0110] The heating program includes:

[0111] (1) heating the vacuum sintering furnace to 1100° C. at a heating rate of 3.1° C. / min and keeping the temperature for 3.5 hours, and then cooling the furnace to obtain high-purity silicon carbide of β-crystal form;

[0112] (2) The vacuum sintering furnace is heated to 10000°C at a heating rate of 2°C / min and kept at this temperature for 8 hours, then the temperature is further heated to 1600°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, then the temperature is further heated to 2300°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and then the furnace is cooled to obtain high-purity silicon carbide of α crystal form.

[0113] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilazane; the impurity content of the mixed powder is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 10MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 5°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2100°C, and after the heat preservation time is 2h, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0114] The obtained silicon carbide ceramic material has an impurity content of 330ppm, a bending strength of 150MPa, a thermal conductivity of 120W / (m·K), and a thermal expansion coefficient of 6K. -1 ×10 -6 , fracture toughness 6MPa·m 1 / 2 .

[0115] Example 10

[0116] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.55, first place the polycrystalline silicon block in a silicon carbide spheroidal graphite tank, and add silicon carbide balls for spheroidal graphite to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 320μm; the spheroidal graphite time is 40h.

[0117] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 11 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.04, and the mass ratio of deionized water to powder is 0.8:1.

[0118] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. Deionized water is continuously added to rinse the filter cake during the suction filtration process until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 110°C for 3.5 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are performed in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 450μm.

[0119] The heating program includes:

[0120] (2) the vacuum sintering furnace was heated to 1300° C. at a heating rate of 10° C. / min and kept at that temperature for 8 hours, and then the temperature was further heated to 1600° C. at a heating rate of 5° C. / min and kept at that temperature for 4 hours, and then the furnace was cooled to obtain high-purity silicon carbide of 4H crystal form;

[0121] (3) The vacuum sintering furnace was heated to 1200°C at a heating rate of 7°C / min and kept at this temperature for 5.5 hours. The temperature was then heated to 1500°C at a heating rate of 3.5°C / min and kept at this temperature for 2.4 hours. The temperature was then heated to 2100°C at a heating rate of 4.5°C / min and kept at this temperature for 2 hours. After the furnace was cooled, high-purity silicon carbide of α crystal form was obtained.

[0122] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilane; the impurity content thereof is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 15MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 4.5°C / min, and argon gas is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2000°C, and after the heat preservation time is 2h, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0123] The obtained silicon carbide ceramic material has an impurity content of 350ppm, a bending strength of 200MPa, a thermal conductivity of 120W / (m·K), and a thermal expansion coefficient of 7K. -1 ×10 -6 , fracture toughness 4MPa·m 1 / 2 .

[0124] Embodiment 11

[0125] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.56, first place the polycrystalline silicon block in a silicon carbide spheroidal graphite tank, and add silicon carbide balls for spheroidal graphite to obtain silicon powder; the obtained silicon powder is sieved and graded to obtain the graded silicon powder, and the size of the graded silicon powder is 240μm; the spheroidal graphite time is 34h.

[0126] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 11 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.03, and the mass ratio of deionized water to powder is 0.7:1.

[0127] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 120°C for 2.6 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are carried out in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 450μm.

[0128] The heating program includes:

[0129] (1) heating the vacuum sintering furnace to 1300° C. at a heating rate of 10° C. / min and keeping the temperature for 2 hours, and then cooling the furnace to obtain high-purity silicon carbide of β-crystal form;

[0130] (2) the vacuum sintering furnace is heated to 1000° C. at a heating rate of 2° C. / min and kept at this temperature for 8 hours, and then the temperature is further heated to 1400° C. at a heating rate of 2° C. / min and kept at this temperature for 4 hours, and then the furnace is cooled to obtain high-purity silicon carbide of 4H crystal form;

[0131] (3) The vacuum sintering furnace was heated to 1200°C at a heating rate of 6°C / min and kept at this temperature for 2 hours, then heated to 1400°C at a heating rate of 5°C / min and kept at this temperature for 1 hour, then heated to 2100°C at a heating rate of 3.5°C / min and kept at this temperature for 1.4 hours, and then cooled in the furnace to obtain high-purity silicon carbide of α crystal form.

[0132] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosiloxane; the impurity content thereof is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 11MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.2MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 7.8°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2000°C, and after the heat preservation time is 2h, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0133] The obtained silicon carbide ceramic material has an impurity content of <500ppm, a bending strength of 210MPa, a thermal conductivity of 125W / (m·K), and a thermal expansion coefficient of 6K -1 ×10 -6 , fracture toughness 3.8MPa·m 1 / 2 .

[0134] Example 12

[0135] Weigh the polycrystalline silicon block and silicon carbide ball in a mass ratio of 0.58, first place the polycrystalline silicon block in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; the obtained silicon powder is sieved and classified to obtain the classified silicon powder, and the size of the classified silicon powder is 400μm; the spherical ink time is 40h.

[0136] The classified silicon powder and high-purity carbon powder are added to a phenolic resin ball mill, and deionized water is used as the grinding medium. Phenolic resin balls are used for wet ball milling, and the ball milling time is 3 hours; the impurity content in the high-purity carbon powder is <400ppm, the molar ratio of silicon powder to carbon powder is 1:1.1, and the mass ratio of deionized water to powder is 0.69:1.

[0137] When grinding is completed, sulfuric acid is added to the ground slurry and grinding is continued; after grinding, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. Deionized water is continuously added to rinse the filter cake during the suction filtration process until the filtrate is clear and the pH is > 4; the filter cake is taken out and dried at 180°C for 3.8 hours; the dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree of less than 1.5 MPa; sintering and insulation are performed in a vacuum sintering furnace under a heating program, and after cooling with the furnace, high-purity silicon carbide powder of different crystal forms is obtained, which is crushed and ground, sieved, and classified to obtain high-purity silicon carbide powder, and the size of the high-purity silicon carbide powder after classification is 450μm.

[0138] The heating program includes:

[0139] (1) heating the vacuum sintering furnace to 1080° C. at a heating rate of 10° C. / min and keeping the temperature for 6 hours, and then cooling the furnace to obtain high-purity silicon carbide of β-crystal form;

[0140] (2) heating the vacuum sintering furnace to 1280° C. at a heating rate of 5° C. / min and keeping the temperature for 2 h, then heating the temperature to 1450° C. at a heating rate of 4.5° C. / min and keeping the temperature for 2.4 h, and then cooling the furnace to obtain high-purity silicon carbide of 4H crystal form;

[0141] (3) The vacuum sintering furnace is heated to 1200°C at a heating rate of 8°C / min and kept at this temperature for 5 hours. The temperature is then continuously heated to 1500°C at a heating rate of 3°C / min and kept at this temperature for 3 hours. The temperature is then continuously heated to 2000-2300°C at a heating rate of 2.2°C / min and kept at this temperature for 1-4 hours. After the furnace is cooled, high-purity silicon carbide of α-crystal form is obtained.

[0142] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is silicon carbide nano whiskers; the impurity content of the mixed powder is less than 400ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 12MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.4MPa, and the vacuum is maintained, and the temperature is increased to 1690°C at a heating rate of 6.6°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2100°C, the heat preservation time is 2.4h, and the furnace is cooled to obtain a high-purity silicon carbide ceramic material.

[0143] The obtained silicon carbide ceramic material has an impurity content of <500ppm, a bending strength of 180MPa, a thermal conductivity of 140W / (m·K), and a thermal expansion coefficient of 6K -1 ×10 -6 , fracture toughness 3.5MPa·m 1 / 2 .

[0144] The present invention also adds a high-purity additive. The good performance brought by the preparation method of the present invention is introduced below through specific examples and comparative examples.

[0145] Example 13

[0146] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosilane, and the impurity content of the mixed powder is 350ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 10MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 0.5MPa, and the vacuum is maintained, and the temperature is increased to 1800°C at a heating rate of 8°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 1900°C, and after the heat preservation time is 1h, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0147] Embodiment 14

[0148] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is polycarbosiloxane, and the impurity content thereof is 375 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 15 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.5 MPa, and the vacuum is maintained, and the temperature is increased to 1700°C at a heating rate of 3°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2200°C, and after the heat preservation time is 4 hours, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0149] Embodiment 15

[0150] A high-purity additive is added to the obtained high-purity silicon carbide powder, and the mixture is stirred evenly to obtain a mixed powder, wherein the additive is silicon carbide nano whiskers, and the impurity content thereof is 367 ppm; the mixed powder is poured into a mold, and a green blank is obtained by dry pressing, and the dry pressing pressure is 15 MPa; the green blank is placed in a vacuum sintering furnace and evacuated to 1.2 MPa, and the vacuum is maintained, and the temperature is increased to 1600°C at a heating rate of 5.5°C / min, and argon is introduced into the vacuum sintering furnace; the vacuum sintering furnace is then heated to 2100°C, and after the heat preservation time is 3 hours, the green blank is cooled with the furnace to obtain a high-purity silicon carbide ceramic material.

[0151] The silicon carbide ceramic materials obtained in Examples 13-15 were subjected to performance tests, and the results are shown in Table 3.

[0152] Table 3 Performance test results of silicon carbide ceramic materials of Comparative Example 1 and Examples 2-4

[0153]

[0154] It can be seen from Table 3 that in the present invention, by using additives, a liquid phase is generated at low temperature during the synthesis process of silicon carbide powder, and liquid silicon carbide is used to initiate the reaction between carbon powder and silicon powder, thereby reducing the difficulty in initiating the reaction due to the high surface energy barrier between carbon powder and silicon powder, and the problem of initiating temperature. By using additives, the reaction temperature is effectively reduced, which plays a role in reducing the energy consumption of synthesis.

[0155] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-purity silicon carbide ceramic material, characterized in that: The ceramic material is a structure prepared by sintering silicon carbide powder prepared by adding additives to silicon carbide powder and high-purity carbon powder; the silicon carbide powder includes one or more of 4H crystal type, β crystal type, and α crystal type, and the additive is polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nano whisker; the molar ratio of silicon powder to carbon powder is silicon powder: high-purity carbon powder = 1:1-1.1; the additive accounts for 0-1% of the total mass of silicon carbide powder and additive powder, and the impurity content in the high-purity carbon powder is <400ppm.

2. The high-purity silicon carbide ceramic material according to claim 1, characterized in that: The density of the high-purity silicon carbide ceramic material is 2.8-3.1 g / cm 3 , porosity is 0-0.5%, impurity content is <500ppm, bending strength is 130-250MPa, thermal conductivity is 110-140W / (m·K), thermal expansion coefficient is 3-8K -1 ×10 -6 , fracture toughness 3~7MPa·m 1 / 2 .

3. A method for preparing high-purity silicon carbide ceramic material, characterized in that: The specific steps of the method include: (1) Preparation and purification of silicon carbide powder (1.1) Weigh a certain mass ratio of polycrystalline silicon blocks and silicon carbide balls, place the polycrystalline silicon blocks in a silicon carbide spherical ink tank, and add silicon carbide balls for spherical ink to obtain silicon powder; (1.2) sieving and classifying the silicon powder obtained in step (1.1) to obtain classified silicon powder; (1.3) adding the classified silicon powder and high-purity carbon powder into a phenolic resin ball mill, using deionized water as the grinding medium and phenolic resin balls for wet ball milling; wherein the impurity content in the high-purity carbon powder is less than 400ppm; (1.4) After the grinding in step (1.3) is completed, sulfuric acid is added to the ground slurry and the grinding is continued; (1.5) After the grinding in step (1.4) is completed, the slurry is transferred to a suction filtration device, and the liquid phase is removed by suction filtration. During the suction filtration process, deionized water is continuously added to rinse the filter cake until the filtrate is clear and the pH is >4; (1.6) taking out the filter cake from step (1.5) and drying it at 80-200° C. for 0.5-5 h; (1.7) The dried filter cake is placed in a graphite mold and placed in a vacuum sintering furnace, and evacuated to a vacuum degree below 1.5 MPa; (1.8) Sintering and heat preservation are performed in a vacuum sintering furnace under a temperature rising program, and high-purity silicon carbide powders of different crystal forms are obtained after cooling in the furnace, and high-purity silicon carbide powders are obtained after crushing and grinding, sieving, and grading; (2) Preparation of silicon carbide ceramic materials (2.1) adding a high-purity additive to the obtained high-purity silicon carbide powder, and stirring the mixture to obtain a mixed powder; (2.2) pouring the mixed powder in step (2.1) into a mold, and preparing a green blank by dry pressing, the dry pressing pressure being 5 to 20 MPa; (2.3) placing the green blank in step (2.2) into a vacuum sintering furnace and evacuating the vacuum to 0.5-1.5 MPa, maintaining the vacuum, and heating the temperature to 1600-1800° C. at a heating rate of 3-8° C. / min, and then introducing argon gas into the vacuum sintering furnace; (2.4) Continue to heat the vacuum sintering furnace in step (2.3) to 1900° C. to 2200° C., keep the temperature for 1 to 4 hours, and then cool the furnace to obtain a high-purity silicon carbide ceramic material.

4. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (1), the mass ratio of polycrystalline silicon block to silicon carbide ball is 1:0.4-0.8; the spherical ink time is 1-48 hours; and the size of silicon powder after classification is 80-400 μm.

5. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (1.3), the molar ratio of silicon powder to carbon powder is 1:1 to 1.

1.

6. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (1.3), the mass ratio of deionized water to powder is 0.6-0.9:

1.

7. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (1.4), the ball milling time is 1 to 20 hours.

8. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: The heating program includes one or more of the following: (1.8.1) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min and kept at this temperature for 2-8 hours. After cooling in the furnace, high-purity silicon carbide of β-crystal form is obtained; (1.8.2) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min, and kept at this temperature for 2-8 hours, and then the temperature is further increased to 1400-1600°C at a heating rate of 2-5°C / min, and kept at this temperature for 1-4 hours, and then cooled in the furnace to obtain high-purity silicon carbide of 4H crystal form; (1.8.3) The vacuum sintering furnace is heated to 1000-1300°C at a heating rate of 2-10°C / min and kept at this temperature for 2-8 hours. The temperature is then raised to 1400-1600°C at a heating rate of 2-5°C / min and kept at this temperature for 1-4 hours. The temperature is then raised to 2000-2300°C at a heating rate of 2-5°C / min and kept at this temperature for 1-4 hours. The furnace is then cooled to obtain high-purity silicon carbide in the α-crystalline form.

9. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (1.8), the size of the high-purity silicon carbide powder obtained after classification is 80 to 500 μm.

10. The method for preparing high-purity silicon carbide ceramic material according to claim 3, characterized in that: In step (2.1), the additive is one or more of polycarbosilane, polycarbosilazane, polycarbosiloxane or silicon carbide nanowhiskers; and the impurity content thereof is less than 400 ppm.

Citation Information

Patent Citations

  • Method for preparing one dimension SiC Nano fiber

    CN101049932A

  • Method for synthesizing high-purity silicon carbide raw material for growing silicon carbide single crystals

    CN102674357A

  • Method for preparing silicon carbide ceramic from silicon carbide solid waste

    CN103086721A

  • Method for preparing carbon fiber reinforced silicon carbide (Csf / C-SiC) composite material

    CN105967712A

  • Pure silicon carbide ceramic membrane component and preparation method thereof

    CN108261928A

Cited By

  • Preparation method of 6N-grade high-purity silicon carbide powder

    CN120463200A

  • Boron-additive-free silicon carbide sintered body as well as preparation method and application thereof

    CN121573991A